Cerita dan tokoh dalam soroton Abdulaziz bin Muhammad As-Sadhan; penerjemah, Husein A. Baraja; editor, Purwanto - ABDULAZIZ BIN MUHAMMAD AS-SADHAN; Baraja, Husein A; Purwanto (Pustaka Mantiq, 1997)
75 hlm. ; 16 cm.